The Narrator as Dubious Witness: Adapting And the Soul Shall Dance for the Stage. Issue 2 (13th April 2016) - Kim, Ju Yon
Abstract : Staged by East West Players in 1977, Wakako Yamauchi's And the Soul Shall Dance became one of the company's most successful and critically acclaimed productions. The drama launched Yamauchi's career as a playwright and helped East West Players (EWP) develop a strong audience base in the Japanese American community in southern California. Set in the 1930s in California's Imperial Valley, the play opens with the Japanese American Murata family surveying the damage caused by the accidental burning of their bathhouse. When the father (referred to only as "Murata" in the play) suggests that they might simply use the tub standing in the midst of razed walls, his wife Hana protests, "Everyone in the country can see us!" Murata quickly dismisses her concerns: "Who? Who'll see us? You think everyone in the country waits to watch us take a bath?" (157). Hana's uneasiness nevertheless injects a fear of scrutiny into the first scene of the play and turns those in the audience into the voyeurs whom she fears.